Analisis Peran Motivasi Kerja dalam Keberhasilan Pencapaian Target Kinerja: Studi Mixed-Method pada Pegawai Bank Syariah Indonesia Cabang Surabaya ITS - M. A. Putri Hidayatuz Zakiyah; Adinda Safitri; Raudatul Anastasya; Siti Mahmudah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Work motivation plays a vital role in the successful achievement of performance targets, particularly in the context of Islamic banking, which emphasizes ethical integrity and operational productivity. This study aims to analyze the role of work motivation in the successful attainment of performance targets among employees at Bank Syariah Indonesia (BSI), Surabaya ITS Branch. A mixed-method approach was employed, combining descriptive qualitative and descriptive quantitative methods through questionnaires (n = 13 respondents), in-depth interviews, participatory observations, and internal document analysis. Qualitative data were analyzed thematically, while the questionnaire results were processed using descriptive statistical analysis. The findings reveal that employees exhibit a very high level of work motivation, primarily driven by intrinsic factors such as achievement, recognition, and career development, and reinforced by extrinsic factors such as incentives and a supportive work environment. Performance records indicate that most segment targets were achieved, with some even exceeding the set standards. This study confirms that work motivation not only influences employees’ perceptions but also has a tangible positive impact on performance achievement. Practically, the findings offer strategic recommendations for Bank Syariah Indonesia management to implement a sustainable humanistic approach grounded in religious values in human resource management. This research also provides a novel contribution by exploring the collective and spiritual dimensions of work motivation within the academically rooted Islamic banking sector.